Curriculum implementation: a case study of Mbetana Public Adult Learning Centre in Limpopo Province - Maponya, Lebeko Valley (My University, 2017)
This study highlights the importance of effective curriculum implementation at a Public Adult Learning Centre in a rural community in Limpopo Province. The purpose of the study was to explore the curriculum implementation facing Mbetana Public Adult Learning Centre (MPALC) with the view to recommend appropriate strategies to improve the centre’s curriculum implementation capabilities. Since the study was premised on the interpretivist paradigm, a qualitative research approach was employed to give a detailed account of the curriculum implementation challenges from the perspective of people with lived experiences of MPALC’s curriculum implementation dynamics. The participants which include six learners, the Centre Manager and two facilitators, were chosen using the purposive sampling method. Purposive sampling was preferred because it gave the researcher an opportunity to target participants deemed to possess authentic accounts of MPALC’s curriculum implementation dynamics. Multiple data sources inclusive of silent observations, semi-structured interviews and document analysis were used to gather data. The study found out that the acute shortage of textbooks and stationery, absence of fit-for purpose learning infrastructure, low employee morale due to poor working conditions, inappropriate teaching methods, and the insensitive use of the English language regardless of the learners being predominantly Tsonga speaking people are some of the challenges that hampered the effective implementation of the curriculum guidelines at MPALC. The study recommends that the Department of Higher Education and Training (DHET) should partner with private companies through the public-private partnership frameworks with the view to improve the MPALC’s operating and financial leverage
Thesis (M.Ed. (Adult Education)) -- University of Limpopo, 2017
Keywords: Curriculum; Curriculum implementation; Strategy; Adult basic education and training; Public adult learning centre; Education -- Curricula; Curriculum planning -- South Africa -- Limpopo; Adult education -- South Africa -- Limpopo; Adult learning -- South Africa -- Limpopo